Karakterisasi Selulosa dari Kulit Buah Kakao (Theobroma cacao L.) pada Berbagai Konsentrasi Hidrogen Peroksida dan Suhu Proses Bleaching - Sena, Putu Widya; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
Cocoa pod husk (CPH) is a byproduct of cocoa processing that is abundant and has a low economical value. CPH cellulose can be obtained using the delignification and bleaching process. This study aimed to determine the effect of hydrogen peroxide (H 2 O 2 ) concentration and bleaching process temperature on the characteristics of CPH cellulose and to determine the best treatment to extract CPH cellulose. This research uses a factorial randomized block design, consists of two factors. The first factor is H 2 O 2 concentration, which consists of 10%, 20%, and 30%. The second factor is bleaching temperature, which consists of 60 o C, 80 o C, and 100 o C. The data were analyzed by analysis of variance and continued with the Tukey test. The observed variables were yield, whiteness index, cellulose, hemicellulose, and lignin content. Best treatments were determined using the effectiveness index. The results showed that H 2 O 2 concentration and bleaching process temperature had a significant effect on yield, whiteness index, cellulose, and lignin content of a bleached CPH. Bleaching temperature had a significant effect, but H 2 O 2 concentration had an insignificant effect on hemicellulose content. Interactions between treatments had a significant effect on whiteness index and cellulose content but had no significant effect to yield, hemicellulose, and lignin content of a bleached CPH. The best treatment was obtained using a combination of 30% H 2 O 2 and 100 o C bleaching temperature, resulting in 16.88±0.12% yield, 59.67±0.50% whiteness index, 70.40±0.44% cellulose, 6.33±0.19%  hemicellulose, and 4.49±0.46% lignin content. Keywords : cellulose, cocoa pod husk, bleaching, hydrogen peroxide, temperature